Prevalence of stroke above forty years. - Mohammad, QD; Habib, M; Hoque, A; Alam, B; Haque, B; Hossain, S; Rahman, KM; Khan, SU (Mymensingh Medical Journal, 2012)
Mymensingh Med J. 2011 Oct;20(4):640-4 The abstract of this article is available on the PubMed website